Social Media, Affective Polarization, and Collective Action in Peru - Ruiz Dodobara, Fernando Gabriel (2024)
Affective polarization has become a worldwide phenomenon that impacts the ability to engage in meaningful dialogue and reflective consideration of different available courses of action. Social media use has been linked to phenomena such as homophily and echo chambers, which contribute to the polarization of attitudes and beliefs. At the same time, social media use has been tied to collective action. This study seeks to analyze the relationship between the political use of social media, affective polarization, and collective action. It proposes two models: the first evaluates the mediating effect of the SIMCA variables in the relationship between the political use of social media and collective action; the second proposes a pathway whereby the political use of social media and its impact on collective action is mediated first by affective polarization and subsequently by the SIMCA model variables. Using a sample of 659 Peruvian social media users ranging from 18 to 39 years old, the authors found that participative efficacy alone mediates the relationship between the political use of social media and collective action. Affective polarization by itself did not mediate this relationship. However, when considering participative efficacy, the findings indicate a pathway from political use of social media to collective action mediated by both affective polarization and participative efficacy. This article reflects on how the production of affective polarization in virtual spaces among like-minded individuals can impact participative efficacy, and subsequently collective action. © 2024 Communication & Society.